Comparison of Quality of Life of Medical Students in Annual and Modular System in Public Sector Medical Colleges in Karachi, Pakistan - Ayema Haque; Sobia Mansoor; Farheen Malik; Jawad Ahmed; Zeba Haque (University Library System, University of Pittsburgh, 2022)
Background: Curriculum structure in medical education in Pakistan includes an annual system which is based on subject wise learning and clinical rotations, and a modular system, with the basic and clinical sciences taught cohesively. The effect of curriculum designs in the quality of life (QoL) of medical students has not been assessed in Pakistan. We aimed to compare these two curriculum structures focused on QoL. Methods: Cross-sectional study of medical students from three different medical schools in Karachi, Pakistan, comparing QoL based on their curriculums. QoL was measured using the WHOQOL-BREF questionnaire. Through random sampling students from each year (1st-5th year) in each institution were selected. Kruskal Wallis test and Mann-Whitney U test were used to compare scores among different years of medical training and between curricular systems. Results: Response rate was 85%. Out of 404 participants, 81.3% were females, and age average was 21±1 years. According to the year of study, significant differences were observed in physical health and overall QoL domain, with 3rd-year students having the highest scores. Overall QoL of students in clinical years was found to be significantly higher than those in preclinical years. The modular system was found to have a better but not significantly higher QoL when compared to the annual system (mean 83.34±11.41 vs. 82.32±10.27, respectively). Conclusion: Overall QoL in the modular system was slightly higher than the annual system, but a significant difference was noted only in the environmental domain. QoL of students in clinical years was higher than preclinical years.